Current and planned research for managing the fruit fly threat to New Zealand - Teulon, David A.J.; Kean, John M.; Armstrong, Karen F. (New Zealand Plant Protection, 2019)
Fruit flies (Family Tephritidae), in particular the Queensland fruit fly (Bactrocera tryoni; QFF), are one of the biggest biosecurity risks for New Zealand horticulture. New Zealand has one of the best science-based biosecurity systems in the world, based on years of experience and sound research. The introduction of fruit flies to New Zealand is now well managed in commercial fruit imports, but the risk is rising from growing trade and travel and, in the case of QFF, climatic adaptation and spread to more southern localities. Smarter solutions are continually needed to manage this increasing risk, and to deal with such pests when they arrive. We present a brief summary of current and anticipated research aimed at reducing the likelihood of entry into New Zealand and/or minimising the impact for the fruit fly species of greatest threat to New Zealand. Research spans risk assessment, pathway risk management, diagnostics, surveillance and eradication.